Lanthanum Strontium Cobalt Ferrite (LSCF) perovskites by Sol-Gel Method for Potential Application in Solid Oxide Fuel Cells (SOFC) (Research, Society and Development, 2022)
Fuel cells are one of the most efficient and effective solutions to environmental problems and high energy demand. They are devices which change chemical energy into electrochemical energy, allowing much higher efficiency than conventional thermomechanical conversion methods. Lanthanum Strontium Cobalt Ferrite (LSCF) perovskites have been widely studied for application as cathodes in solid oxide fuel cells (SOFC) due to their high electrical conductivity, high thermal and chemical stability, low difference in thermal expansion coefficient, and physico-chemical compatibility with the other cells components. The aim of this work was to synthesize perovskitas type La0.7Sr0.3Co0.5Fe0.5O3 by sol-gel method and evaluate the potential for application as a cathode for fuel cell. The results obtained by X-ray powder diffraction (XRD) indicate that the sol-gel method calcined at 900ºC obtained an amount of the perovskite phase above 95%. The Field Emission Gun-Scanning Electron Microscope (FEG-SEM) images of LSCF film produced with 4 layers showed a better quality. Thus, the results obtained by XRD and FEG-SEM, indicate that the sol-gel method calcined at 900ºC has a potential application as cathode in solid oxide fuel cells.